2023
DOI: 10.1161/circheartfailure.122.010158
|View full text |Cite
|
Sign up to set email alerts
|

In-Hospital Virtual Peer-to-Peer Consultation to Increase Guideline-Directed Medical Therapy for Heart Failure: A Pilot Randomized Trial

Abstract: Background: Guideline-directed medical therapy (GDMT) for heart failure with reduced ejection fraction (HFrEF) improves clinical outcomes and quality of life. Optimizing GDMT in the hospital is associated with greater long-term use in HFrEF. This study aimed to describe the efficacy of a multidisciplinary virtual HF intervention on GDMT optimization among patients with HFrEF admitted for any cause. Methods: In this pilot randomized, controlled study, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Both studies found significant increases in prescription rates of GDMT at discharge, though findings were not consistent across studies. For instance, while IMPLEMENT-HF reported increases in β-blockers (93.4% vs 82.5%; P = .01) and MRAs (49.1% vs 21.0%; P = .02), Rao et al showed increases in ACEi, ARB, and ARNI prescriptions (71% vs 49%; P = .04).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both studies found significant increases in prescription rates of GDMT at discharge, though findings were not consistent across studies. For instance, while IMPLEMENT-HF reported increases in β-blockers (93.4% vs 82.5%; P = .01) and MRAs (49.1% vs 21.0%; P = .02), Rao et al showed increases in ACEi, ARB, and ARNI prescriptions (71% vs 49%; P = .04).…”
Section: Resultsmentioning
confidence: 99%
“…The most common type of intervention was interdisciplinary interventions (n = 15). These studies were further categorized as interdisciplinary heart failure clinics, outpatient audits, or inpatient audits …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The virtual care team consisted of cardiologists and pharmacists and the consultation was directed to clinicians of non-cardiology departments. [ 28 ]. In this single-center randomized controlled trial (RCT), an increase in the proportion of patients on angiotensin-converting enzyme inhibitors (ACE-I)/angiotensin receptor blockers (ARB)/ARNI was demonstrated.…”
Section: Methodsmentioning
confidence: 99%
“…This approach resulted in increased utilization of renin-angiotensin-aldosterone system/neprilysin inhibitors and higher optimal medical therapy scores at discharge compared with the usual care group. 8 Bhatt and colleagues utilized an EHR-generated report to identify hospitalized patients eligible for GDMT optimization and a virtual care team (centralized physician and local pharmacist) to communicate recommendations for optimizing GDMT with the treating clinicians. This strategy led to intensification of GDMT and higher optimization scores compared with usual care.…”
mentioning
confidence: 99%